PELANGGARAN KEKUDUSAN JANJI NAZIR SIMSON SEBAGAI PERINGATAN BAGI ORANG KRISTEN MASA KINI - Serepina Hasibuan; Richard Adiputra Tadu (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2023)
Nazirite is one of the distinctive statuses found in the Old Testament. However, the concept of Naziriteship in the Old Testament is still rarely discussed. Reviewing one of the Nazirs in the Old Testament, namely Samson, creates a lot of confusion because his Nazirite status contradicts his behavior. Therefore, this article is about to examine Samson's destiny and how wicked his behavior was. Then was the suffering at the end of his life related to the breaking of his Nazi vows. This study uses a descriptive qualitative method that examines the text in narrative form and reflects on it for today's Christians. The results obtained from this study are that Samson clearly violated the sanctity of his vows so that he received God's punishment. But on the other hand, God's grace is still there for Samson especially for the people of Israel. Furthermore, today's Christians are God's Nazirs who must reflect God's holiness in living in this world. The promise of self-sanctification must not be broken so that we are not punished by God.